2015
DOI: 10.1371/journal.pone.0119364
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol Production by Fermenting Yeast Cells Is Essential for Optimal Bread Dough Fermentation

Abstract: Glycerol is the main compatible solute in yeast Saccharomyces cerevisiae. When faced with osmotic stress, for example during semi-solid state bread dough fermentation, yeast cells produce and accumulate glycerol in order to prevent dehydration by balancing the intracellular osmolarity with that of the environment. However, increased glycerol production also results in decreased CO2 production, which may reduce dough leavening. We investigated the effect of yeast glycerol production level on bread dough ferment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 36 publications
2
31
0
2
Order By: Relevance
“…Among alcohols, significant amounts of glycerol (0.25%) and ethanol (1.86%) were identified. According to the literature, a high amount of glycerol was the result of yeast (Aslankoohi, Rezaei, Vervoort, Courtin, & Verstrepen, 2015) and hetero‐fermentative LAB activity (Brandt & Ganzle, 2015) as well as lipid hydrolysis by lipases which are both found in rye flour (Banu, Vasilean, & Aprodu, 2011). Ethanol was produced by yeasts present in the flour and added as an ingredient of LV2 cultures (Lefebvre et al, 2002; Van der Meulen et al, 2007) as well as by hetero‐fermentative LAB (Corsetti & Settanni, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Among alcohols, significant amounts of glycerol (0.25%) and ethanol (1.86%) were identified. According to the literature, a high amount of glycerol was the result of yeast (Aslankoohi, Rezaei, Vervoort, Courtin, & Verstrepen, 2015) and hetero‐fermentative LAB activity (Brandt & Ganzle, 2015) as well as lipid hydrolysis by lipases which are both found in rye flour (Banu, Vasilean, & Aprodu, 2011). Ethanol was produced by yeasts present in the flour and added as an ingredient of LV2 cultures (Lefebvre et al, 2002; Van der Meulen et al, 2007) as well as by hetero‐fermentative LAB (Corsetti & Settanni, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Production of more glycerol has been suggested to lead to a decrease in the ratio of reduced form of nicotinamide adenine dinucleotide (NADH) over oxidized form (NAD + ) in the cells. The yeast might balance this ratio through conversion of more acetaldehyde to acetic acid and NADH (Aslankoohi et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Δidh1Δidp1, which might be due to the changes in the ratio of NADH/ NAD + upon a slightly higher production of acetic acid in this sample compared to the wild-type reference strain S288C. Aslankoohi et al (2015) showed that overexpression of GPD1 and a rise in the level of glycerol during dough fermentation has a positive influence on dough stability during fermentation. However, the highest glycerol content observed in this study (5 mmol/100 g flour) is well below the levels they obtained in their GPD1 overexpression strain (12 mmol/100 g flour).…”
Section: Strains Concentration Of Metabolites (Mmol/mol Ethanol) In Fmentioning
confidence: 79%